Mechanical Testing of 3D Metal Printed Stainless Steel Specimens - Kovács, Sándor Endre; Varga, László (International Journal of Engineering and Management Sciences, 2023)
Additive manufacturing (AM) is a cutting-edge production method, which has come a long way since its first introduction in the ’80s. Back in the days its usage was very limited to stereolithography, and was only able to make weak structures, so it only worked for visualization. Four decades later it is one of the leading research fields in production areas, because of its flexibility and its ability to make almost any complex geometry. However, no matter how powerful it is, it is not omnipotent, there are certain size and shape restrictions even this method must apply to.